(untitled) (Conferencea, 2024)
According to a widespread explanation, professional burning is a chronic, negative, service -related mood in individuals, characterized by depletion, accompanied by stress, a reduced sense of efficiency, reduced motivation, and the development of dysfunctional attitudes and behavior. Consequently, it is important for a person to be able to regulate their emotions. The regulation of emotions implies the combination of all processes involved in monitoring, evaluating and transforming the emotional reaction. Cognitive Regulation of Emotion - This is the answer to emotionogenic stimuls that allows a person to control his or her emotional state.